Recent Developments in Statutory and Constitutional Interpretation. (17th December 2018) - Walshaw, Christopher
Abstract: In previous articles, I have promoted concurrent interpretation, also called characterization, as good judicial practice in preference to attempts at prospective interpretation made in advance of application to the facts of the case. I now consider a suggestion that concurrent interpretation does no more than describe what actually happens in adjudication and the consequent challenge to my contentions that there is a difference between concurrent and prospective interpretation, and that such difference matters. This challenge provides an opportunity to re-orientate my critique of prospective interpretation. I argue that in the process of prospective interpretation the object of interpretation may become a different object and that this different object becomes the subject of application. I describe how this happens and discuss the implications. But first I establish a platform for my argument.